Are fear memories erasable?–reconsolidation of learned fear with fear-relevant and fear-irrelevant stimuli - Golkar, Armita; Bellander, Martin; Olsson, Andreas; Öhman, Arne (Frontiers in Behavioral Neuroscience, 2012)
Recent advances in the field of fear learning have demonstrated that a single reminder exposure prior to extinction training can prevent the return of extinguished fear by disrupting the process of reconsolidation. These findings have however proven hard to replicate in humans. Given the significant implications of preventing the return of fear, the purpose of the present study was to further study the prerequisites for the putative effects of disrupting reconsolidation. In two experiments, we assessed whether extinction training initiated within the reconsolidation time window could abolish the return of fear using fear-relevant (experiment 1) or fear-irrelevant (experiment 2) conditioned stimuli (CS). In both experiments, participants went through conditioning, extinction and reinstatement testing on three consecutive days, with one of two reinforced CS being reactivated 10 minutes prior to extinction. We found that a single reminder exposure prior to extinction training did not prevent the return of extinguished fear responding using either fear-relevant or fear-irrelevant CSs. Our findings point to the need to further study the specific parameters that enable disruption of reconsolidation.